2021
DOI: 10.3138/cjpe.69577
|View full text |Cite
|
Sign up to set email alerts
|

Competency-Based Evaluation Education: Four Essential Things to Know and Do

Abstract: Evaluator education must provide robust opportunities to support and assess the progressive, lifelong development of relevant knowledge and skills. If we wish to keep pace with the increasingly complex contexts in which evaluators operate, we need to better align our educational approaches with the global movement towards practice competencies guiding the profession. Key among the challenges is the lack of instructional guidance specific to a competency-based approach to evaluator education. In this practice n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Incorporating evaluator competencies was one of the recurrent recommendations throughout the literature, and it was identified that incorporating these competencies as student learning outcomes was the most effective way to align evaluation practices with industry needs and prepare students for professional practice (Gokiert et al, 2021; LaVelle & Galport, 2020; Poth & Searle, 2021). Of these professional competencies, the most important for practice were identified by Galport and Azzam (2017) as professional practice, systematic inquiry and interpersonal competence, which were also the competencies the study identified as needing the most training.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating evaluator competencies was one of the recurrent recommendations throughout the literature, and it was identified that incorporating these competencies as student learning outcomes was the most effective way to align evaluation practices with industry needs and prepare students for professional practice (Gokiert et al, 2021; LaVelle & Galport, 2020; Poth & Searle, 2021). Of these professional competencies, the most important for practice were identified by Galport and Azzam (2017) as professional practice, systematic inquiry and interpersonal competence, which were also the competencies the study identified as needing the most training.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed by Quadrelli and colleagues, many of these education‐focused articles may be attributed to the efforts of a few scholars soliciting and editing Special Issues for Canadian Journal of Program Evaluation , New Directions for Evaluation , and Evaluation and Program Planning . Topics have included broad landscapes of evaluator education (Gullickson et al., 2019; King & Ayoo, 2020), alignment of graduate education and evaluator competencies (LaVelle & Galport, 2020; LaVelle & Johnson, 2022; Poth & Searle, 2021; Sowl et al., 2022), cognitive complexity (Clinton & Hattie, 2021), service learning (Warner, 2020), authentic course assessments (Searle & Poth, 2021), student and practitioner reflections (LaVelle & Yang, 2021), dispositions (Davies, 2021), incorporation of evaluative thinking (Archibald, 2021), considerations for mentoring graduate students of color (Boyce, 2021), and the teaching and learning of evaluation with and within BIPoC communities.…”
Section: Recent Developments In Evaluator Educationmentioning
confidence: 99%